An Overview of Entrepreneurial Universities and Main Barriers to Entrepreneurial University Development in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
This article aims to study world experience of entrepreneurial universities and reveal main barriersto the development of entrepreneurial education in Kazakhstan. The study was carried out usingsecondary data, in particular global university entrepreneurship reports, scientific articles of localand foreign scientists, and legislative acts. World experience shows that entrepreneurial universitiesmore fully meet innovation needs of the economy and business in the field of education, beingeducational, research and industrial centers. Results of this study reveal that for successful developmentof entrepreneurial university it is important to create mechanisms of transformation of classicaleducation, and take measures for creating favorable external and internal conditions to ensure thestrategic interaction in the system “University-Business-Government”. Regardless of the approachesapplied in different countries, entrepreneurship is recognized as the most important area of education.